Comparative analysis of vitamin K levels in women with intrahepatic cholestasis of pregnancy - Maria Cemortan; Irina Sagaidac; Olga Cernetchi (BMC Pregnancy and Childbirth)
Abstract Background Intrahepatic cholestasis of pregnancy (ICP) is a liver condition that may impact both mother and fetus, including preterm birth and hemorrhage. Vitamin K, a fat-soluble vitamin essential for coagulation, may be deficient in ICP due to impaired bile flow, raising hemorrhage risk. The study aimed to analyze Vitamin K1, K2 MK4, and K2 MK7 levels in pregnant women with ICP and determine associations between Vitamin K deficiency and postpartum hemorrhage. Methods This prospective cohort study included 44 pregnant women with ICP (L1) and 44 controls (L0). Serum Vitamin K levels, using high-performance liquid chromatography, and blood loss during delivery were assessed. Statistical analyses included t-tests and chi-square tests, with significance at p < 0.05. Study registration number ISRCTN21187408 https://www.isrctn.com/ISRCTN21187408 Registration date 03/06/2020. Results Women with ICP exhibited significantly lower mean levels of Vitamin K1 (0.15 ± 0.17 µg/L in L1 vs. 0.29 ± 0.30 µg/L in L0, p = 0.0085) and Vitamin K2 MK7 (0.17 ± 0.13 µg/L in L1 vs. 0.26 ± 0.14 µg/L in L0, p = 0.0024) compared to controls. Vitamin K1 deficiency was observed in 52.3% of the ICP group vs. 2.3% in controls. Mean blood loss during vaginal delivery was higher in the ICP group (351 ± 104 mL in L1 vs. 297 ± 87 mL in L0, p = 0.0373). Conclusions This study suggests that ICP contributes to significant Vitamin K1 deficiency in pregnant women, potentially increasing postpartum hemorrhage risk. Routine Vitamin K monitoring and possible supplementation with vitamin K in pregnant women with ICP may be beneficial to mitigate adverse maternal outcomes. Further research is warranted to confirm these findings.